(untitled) (Jurnal AbdiMas Nusa Mandiri, 2026)
This community service program aims to strengthen community capacity in Prabu Tourism Village through the EDUKARSA (Education and Creation for the Community) program, which integrates four key capacity-building components: culinary presentation, homestay room preparation, tour package development, and photography and videography for digital content creation. The program was implemented using a Participatory Action Research (PAR) approach involving 40 participants from June to October 2025 through stages of planning, implementation, evaluation, and sustainability. Program effectiveness was evaluated using a structured questionnaire with a five-point Likert scale, analyzed descriptively using statistical procedures commonly applied in SPSS. The results show that the overall mean score of participants’ competency improvement reached 4.42 (SD = 0.51), indicating a high level of perceived effectiveness. Reliability testing demonstrated strong internal consistency, with a Cronbach’s Alpha value of 0.91, confirming that the evaluation instrument was highly reliable. Improvements were most notable in culinary presentation (mean = 4.55), homestay management (mean = 4.48), tour package design (mean = 4.36), and digital content production (mean = 4.29). Despite these positive outcomes, several challenges remain, particularly in standardizing homestay facilities, determining competitive tour package pricing, and strengthening community-based documentation teams. Overall, the EDUKARSA program significantly contributed to enhancing human resource capacity and reinforcing Prabu Village as a sustainable, community-based tourism destination supported by quality services and effective digital promotion.